Numerical solutions by EFGM of MHD convective fluid flow past a vertical plate immersed in a porous medium in the presence of cross diffusion effects via biot number and convective boundary condition - Raju, R. Srinivasa; Reddy, B. Mahesh; Rashidi, M. M.; Gorla, Rama Subba Reddy (Zielona Góra: Uniwersytet Zielonogórski)
In this investigation, the numerical results of a mixed convective MHD chemically reacting flow past a vertical plate embedded in a porous medium are presented in the presence of cross diffusion effects and convective boundary condition. Instead of the commonly used conditions of constant surface temperature or constant heat flux, a convective boundary condition is employed which makes this study unique and the results more realistic and practically useful.
Keywords: thermal diffusion; diffusion thermo; MHD; porous medium; EFGM